C4b‐binding protein negatively regulates TLR4/MD‐2 response but not TLR3 response. Issue 12 (12th June 2017) - Morita, Naoko; Yamazaki, Tatsuya; Murakami, Yusuke; Fukui, Ryutaro; Yamai, Ikuko; Ichimonji, Isao; Nakashima, Akina; Nagaoka, Fumiaki; Takagi, Hidekazu; Miyake, Kensuke; Akashi‐Takamura, Sachiko
Abstract : Recently, we reported a novel function for C4b‐binding protein (C4BP) in inhibiting the toll‐like receptor (TLR)1/2 response by interacting with TLR2. TLRs share a common structure; hence, we examined the effect of C4BP on activation of other TLRs—TLR4 and TLR3. The results of immunoprecipitation assays suggest that C4BP interacts with TLR4/MD‐2 but not TLR3. C4BP inhibits TLR4/MD‐2‐mediated, but not TLR3‐mediated, proinflammatory cytokine production and nuclear factor (NF)‐κB signaling. C4BP‐deficient mice show increased interleukin (IL)‐6 production in response to the TLR4/MD‐2 ligand. A competition assay revealed that C4BP prevents an interaction between TLR4/MD‐2 and its ligand. These findings indicate that C4BP binds to cell surface TLRs and inhibits the TLR–TLR ligand interaction, thereby inhibiting TLR activation. Abstract :